The lateral mesodermal divide: an epigenetic model of the origin of paired fins. Issue 1 (6th January 2014) - Nuño de la Rosa, Laura; Müller, Gerd B.; Metscher, Brian D.
SUMMARY By examining development at the level of tissues and processes, rather than focusing on gene expression, we have formulated a general hypothesis to explain the dorso‐ventral and anterior–posterior placement of paired appendage initiation sites in vertebrates. According to our model, the number and position of paired appendages are due to a commonality of embryonic tissue environments determined by the global interactions involving the two separated layers (somatic and visceral) of lateral plate mesoderm along the dorso‐ventral and anterior–posterior axes of the embryo. We identify this distribution of developmental conditions, as modulated by the separation/contact of the two LPM layers and their interactions with somitic mesoderm, ectoderm, and endoderm as a dynamic developmental entity which we have termed the lateral mesodermal divide (LMD). Where the divide results in a certain tissue environment, fin bud initiation can occur. According to our hypothesis, the influence of the developing gut suppresses limb initiation along the midgut region and the ventral body wall owing to an "endodermal predominance." From an evolutionary perspective, the lack of gut regionalization in agnathans reflects the ancestral absence of these conditions, and the elaboration of the gut together with the concomitant changes to the LMD in the gnathostomes could have led to the origin of paired fins.